2021
DOI: 10.1177/10384162211008888
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between locus of control and hope in adolescents: The mediating role of career and talent development self-efficacy

Abstract: Adolescence is a period that plays a crucial role in career development. Understanding the psychological structures associated with a career can help to better understand adolescents’ career development. The aim of this study was to examine the mediating role of career and talent development self-efficacy in the relationship between adolescents’ locus of control and the construct of children’s hope. The study group was composed of 354 adolescents including 170 females and 184 males. The mean age of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
(103 reference statements)
1
2
0
Order By: Relevance
“…Hypothesis six of this study, assumed that talent development mediates the relationship between transactional leadership and talent engagement. The results endorsed the mediating effect of talent development in the relationship between transactional leadership and talent engagement, which is consistent with the study by Turan (2021). Since transactional leaders can influence their subordinates for their development (Masa'deh et al., 2016) and talent development directly impacts engagement (Ali et al., 2020), so the current results stressed the mediating role of talent development in the association between transactional leadership and talent engagement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hypothesis six of this study, assumed that talent development mediates the relationship between transactional leadership and talent engagement. The results endorsed the mediating effect of talent development in the relationship between transactional leadership and talent engagement, which is consistent with the study by Turan (2021). Since transactional leaders can influence their subordinates for their development (Masa'deh et al., 2016) and talent development directly impacts engagement (Ali et al., 2020), so the current results stressed the mediating role of talent development in the association between transactional leadership and talent engagement.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, it was found that talent development mediates the relationship between HRM practices and innovative behavior (Datta et al., 2021). Turan (2021) supported the mediating impact of talent development between locus of control and hope in adolescents. Another recent research evidence also demonstrates the mediating influence of talent development (Younas & Waseem Bari, 2020) between the association of TM practices and retention particularly in the case of generation Y employees.…”
Section: Development Of Hypothesesmentioning
confidence: 94%
“…Because unemployment is a strong predictor of poverty, job readiness programs are important for youth who live in poverty, as securing permanent employment would offer income in the form of wages and benefits (Paul et al, 2018). In contrast, poor job-readiness skills among young adults may hinder important critical skills and job-related experiences, which can lead to decreased employability skills (Turan, 2021) and low wages in adulthood (Lim and Mitchell, 2017).…”
Section: Addressing Intergenerational Povertymentioning
confidence: 99%